2013
DOI: 10.1214/12-aoas593
|View full text |Cite
|
Sign up to set email alerts
|

Estimating treatment effect heterogeneity in randomized program evaluation

Abstract: When evaluating the efficacy of social programs and medical treatments using randomized experiments, the estimated overall average causal effect alone is often of limited value and the researchers must investigate when the treatments do and do not work. Indeed, the estimation of treatment effect heterogeneity plays an essential role in (1) selecting the most effective treatment from a large number of available treatments, (2) ascertaining subpopulations for which a treatment is effective or harmful, (3) design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
357
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(371 citation statements)
references
References 56 publications
2
357
1
Order By: Relevance
“…Imai and Ratkovic [2013], Signorovitch [2007], Tian et al [2014] and Weisberg and Pontes [2015] develop lasso-like methods for causal inference in a sparse high-dimensional linear setting. Beygelzimer and Langford [2009], Dudík et al [2011], and others discuss procedures for transforming outcomes that enable off-the-shelf loss minimization methods to be used for optimal treatment policy estimation.…”
Section: Related Workmentioning
confidence: 99%
“…Imai and Ratkovic [2013], Signorovitch [2007], Tian et al [2014] and Weisberg and Pontes [2015] develop lasso-like methods for causal inference in a sparse high-dimensional linear setting. Beygelzimer and Langford [2009], Dudík et al [2011], and others discuss procedures for transforming outcomes that enable off-the-shelf loss minimization methods to be used for optimal treatment policy estimation.…”
Section: Related Workmentioning
confidence: 99%
“…Imai and Ratkovic (2013) estimate a LASSO regression model with the treatment indicator interacted with covariates, and uses LASSO as a variable selection algorithm for determining which covariates are most important. In using this approach, it may be prudent to perform some supplementary analysis to verify that the method is not overfitting; for example, one could use a sample-splitting approach, using half of the data to estimate the LASSO regression and then comparing the results to an ordinary least squares regression with the variables selected by LASSO in the other half of the data.…”
Section: Machine Learning For Heterogenous Causal Effectsmentioning
confidence: 99%
“…The reason why we compare our sHinge method with the ROWSi is that Xu et al (2015) showed by simulation that the ROWSi was superior over the method solving (9) with h k replaced by the hinge loss, which was proposed in Zhao et al (2012) except that LASSO penalty instead of L 2 penalty was used for variable selection. Xu et al (2015) also showed by simulation that ROWSi was superior over other four recently proposed methods, the interaction tree by Su, Tsai, Wang, Nickerson, and Li (2009), the virtual twins by Foster, Taylor, and Ruberg (2011), the logistic regression with LASSO penalty by Qian and Murphy (2011), and the FindIt by Imai and Ratkovic (2013).…”
Section: Simulation Resultsmentioning
confidence: 89%